The Loud Crowd: Using Vocal Responses to Understand the Emotional Experiences of Spectators - Matthew Katz; Bob Heere; Katherine Reifurth (Journal of Applied Sports Management, 2018)
Much research has been conducted on the relationship between emotions and the sport experience, but most research in this field has used survey data, which has proven to have many limiting factors when attempting to measure emotions. Rather than relying on surveys, the present study uses a more direct measure of consumer emotion: sound. By measuring the variations in sound levels among sport attendees, the present study provides an exploratory study of sport fan emotions through behavioral indicators of emotional experiences rather than cognitive recall. Our results indicate that the strongest vocal responses were consistently in response to surprising plays, not necessarily plays most beneficial to the home team. These results from increase our understanding of the emotional experience of sport attendees and provide insight into how to expand and maximize the emotional responses of sport spectators to create a stronger connection between team and consumer. Subscribe to JASM
Keywords: sound; sport; experience; emotion